KEWENANGAN PIHAK KEPOLISIAN YANG MENANGANI PERKARA PIDANA DALAM PROSES PENYIDIKAN KAITANNYA DENGAN LOCUS DELICTI - Darius Timotius Usat (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT The relationship between the construction of the scene is to give a description of the suspect made by investigators for the purposes of criminal investigations to be adapted to conditions in the real scene. In practice, the reconstruction was not done in the actual crime scene. It is solely for the safety of the suspect himself in order to avoid the wrath of the people. Besides for that, as well as to suppress the reconstruction costs to a minimum, especially if the scene in which the reconstruction would be held to be outside the city. But if the scene is not located outside the city, the implementation of reconstruction is still being done in the actual crime scene.If the crime scene was not yet known with certainty, the efforts undertaken are: Doing action by way of prosecution is a technique of investigation that a criminal case was revealed, where the technique of these investigations will obtain the answers to these questions in terms of investigating a criminal case; To conduct the interrogation of the reporting the incident and request information from the patient witnesses, expert witnesses and witnesses who know the first time this criminal case. Despite the regional differences between the crime scene with the area where the discovery of the victim or the proceeds of crime does not preclude the police to uncover the criminal case, because despite differences in the area of the police are still able to work together with each other.